2008
DOI: 10.2500/ajr.2008.22.3162
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Genes in Chronic Rhinosinusitis with and without Nasal Polyps

Abstract: Background-Genetic studies on chronic inflammatory diseases have resulted in an emphasis on the epithelial interface with the environment and the genes that influence this interaction. This study examines the expression of key epithelial genes implicated in the pathogenesis of other inflammatory disorders for their role in chronic rhinosinusitis (CRS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 32 publications
7
76
1
2
Order By: Relevance
“…The polypoid form of CRS and a Th2 cytokine milieu have been associated with significantly decreased levels of AJC proteins [498][499][500][501] as well as diminished intrinsic protective antiprotease activity. 486,502 Functional studies have also documented increased barrier permeability in CRSwNP. 500,501,503 It has been further proposed that the protein oncostatin M may play a key role mediating a leaky barrier in polyps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The polypoid form of CRS and a Th2 cytokine milieu have been associated with significantly decreased levels of AJC proteins [498][499][500][501] as well as diminished intrinsic protective antiprotease activity. 486,502 Functional studies have also documented increased barrier permeability in CRSwNP. 500,501,503 It has been further proposed that the protein oncostatin M may play a key role mediating a leaky barrier in polyps.…”
Section: Discussionmentioning
confidence: 99%
“…490 It has been further suggested that the various phenotypes of CRS, including with or without NPs, may be associated with distinct upstream epithelial defect patterns. 486,491,492 The mechanical component of the barrier consists of 2 parts, respiratory mucus and underlying epithelium. Respiratory mucus traps foreign material and it is moved toward the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 However, cell damage or activation of phagocytes triggers their release into the extracellular space, where they have bacteriostatic properties and become danger signals that activate immune cells and vascular endothelium through interaction with TLR4 or receptor for advanced glycation end products, amplifying the host response to pathogen-derived factors, such as LPS. In an analysis of epithelial genes in patients with chronic rhinosinusitis, expression of S100A8 and S100A9 mRNA was significantly decreased when compared with that seen in control subjects, 73 suggesting this might impair epithelial repair responses in patients with chronic rhinosinusitis. Although intracellular expression of S100A8 and S100A9 has not been evaluated in patients with asthma, a proteomic survey of induced sputum has reported higher levels of calgranulin A (S100A8) in patients with asthma, 59 suggesting that it might trigger an inflammatory response by acting as a damage-associated molecular pattern.…”
Section: Epithelial Innate Immune Responsesmentioning
confidence: 98%
“…S100 proteins also show the typical parameters of DAMPs when released to the extracellular milieu, where they activate TLR4 (Vogl et al, 2007;Loser et al, 2010) and possibly RAGE (Sparvero et al, 2009). Expression of S100A7, S100A8, and S100A9 mRNA is decreased in CRSsNP and CRSwNP when compared with controls (Richer et al, 2008). S100A7 proteins are reduced in the epithelium and glandular structures of CRSwNP tissues using immunohistochemistry, and levels of S100A7 are diminished in nasal lavage fluid of these patients (Tieu et al, 2010).…”
Section: Damage Associated Molecular Patternsmentioning
confidence: 93%